2019
DOI: 10.1002/mde.3082
|View full text |Cite
|
Sign up to set email alerts
|

Tax avoidance in different firm types and the role of nonfamily involvement in private family firms

Abstract: This study simultaneously distinguishes between private family firms, private nonfamily firms, public family firms, and public nonfamily firms. We show that private family firms avoid taxes less than public family firms and public nonfamily firms; however, we do not find a difference between private family firms and private nonfamily firms. Therefore, building on family firm heterogeneity, our results indicate that tax avoidance in private family firms differs depending on the involvement of nonfamily owners a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 116 publications
(194 reference statements)
1
30
0
1
Order By: Relevance
“…In addition, while a large body of literature has focused on the comparison between family and non-family firms, private and public firms, or large and small private firms, few studies have analysed the extent to which the well-known heterogeneity of family firms (Brigham et al, 2019;Chua et al, 2012;Stanley et al, 2019) may affect their tax decisions and thus influence the differences in behaviour compared to non-family firms. Brune et al (2019) found family involvement in firm management has a positive effect on active tax avoidance, compared to non-family firms. Kovermann and Wendt (2019) showed that tax avoidance is positively related to the percentage of family ownership.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…In addition, while a large body of literature has focused on the comparison between family and non-family firms, private and public firms, or large and small private firms, few studies have analysed the extent to which the well-known heterogeneity of family firms (Brigham et al, 2019;Chua et al, 2012;Stanley et al, 2019) may affect their tax decisions and thus influence the differences in behaviour compared to non-family firms. Brune et al (2019) found family involvement in firm management has a positive effect on active tax avoidance, compared to non-family firms. Kovermann and Wendt (2019) showed that tax avoidance is positively related to the percentage of family ownership.…”
Section: Introductionmentioning
confidence: 90%
“…First, we focus on tax aggressiveness in a family firm context taking into account the heterogeneous behaviour of the different generations in control (Chirico et al, 2011), as family firms should not be analysed as a homogeneous entity (Westhead & Howorth, 2007). We go beyond most of the existing research that studies the difference between private and public family firms (Brune et al, 2019), private family firms and private non-family firms (Koverman & Wendt, 2019;Monterry & Sánchez, 2010), or public family firms and public non-family firms (Gaaya et al, 2017). It is worth noting that generational transition is one of the most sensitive processes in family firms (Miller et al, 2003;Molly et al, 2010); as such, further research is needed on this topic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tax avoidance is positively associated with bank loans and loan costs (Beladia et al, 2018). Private family firms avoid taxes less than public family and nonfamily firms (Brune et al, 2019). Tax cuts and credits generate an important impact on firm investments and capital allocation (Altug et al, 2009; Ayuso et al, 2018; Danielova & Sarkar, 2011; Dobbins & Jacob, 2016; Haga et al, 2019; Hines & Park, 2019; Marekwica, 2012; Muthitacharoen, 2021; Sarkar, 2012).…”
Section: Introductionmentioning
confidence: 99%